Current medical education improves OSA-related knowledge but not confidence in residents: An underappreciated public health risk - Su, Linfan; Chen, Ruxuan; Luo, Jinmei; Xiao, Yi (Frontiers in Psychiatry, 2022)
Background Obstructive sleep apnea (OSA) is the most common sleep-related breathing disorder and induces a growing health care burden. However, a large proportion of patients with OSA do not receive appropriate treatment and are underdiagnosed or misdiagnosed in primary care. A contributing factor to the phenomenon is the lack of education, which reflects the current inadequacies in medical education. Therefore, assessing the level of knowledge and attitudes toward OSA and associated factors among resident physicians is highly warranted. Methods A validated questionnaire, the OSA Knowledge and Attitudes (OSAKA) questionnaire was distributed to residents who had already completed undergraduate education and were attending an internal medicine residency training program. The questionnaire consists of 2 parts: including an assessment of (1) OSA-related knowledge involving epidemiology, pathophysiology, clinical manifestations, diagnosis, and treatment; (2) the importance of OSA and confidence in diagnosing and treating OSA patients. Other information including demographics, training experience, and questions exploring the future form of the sleep breathing disorder course was collected together. Results Of the 160 residents who participated in the survey, 153 (95.6%) completed the survey and the mean total knowledge score was 12.6/18 (70% correct). Although all respondents believed that OSA was an important clinical disorder, only a minority of the residents felt confident in identifying patients at risk for OSA (38%), managing OSA patients (27.5%), or continuous positive airway pressure therapy (CPAP) (26.2%). We found that OSA training experience significantly increased knowledge scores (p = 0.002) but not confidence scores (p = 0.248). As for the specific form of medical education, “Small classes during residency training” was the most popular form of sleep-breathing disorder educational training in the future of the resident training program. Conclusion Despite adequate knowledge of OSA, there was still a generalized lack of confidence in the management of OSA patients among residents. Current medical education can not build enough confidence for physicians, which may in turn affect patients' trust and reduce long-term compliance. Untreated OSA places a significant health threat and economic burden on not only the patients but also their families and society, causing an underappreciated public health risk. In the future, merely increasing OSA courses is not sufficient, a more specific focus on the course format and training effect is required.